2017
DOI: 10.1038/s41540-017-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

A Clb/Cdk1-mediated regulation of Fkh2 synchronizes CLB expression in the budding yeast cell cycle

Abstract: Precise timing of cell division is achieved by coupling waves of cyclin-dependent kinase (Cdk) activity with a transcriptional oscillator throughout cell cycle progression. Although details of transcription of cyclin genes are known, it is unclear which is the transcriptional cascade that modulates their expression in a timely fashion. Here, we demonstrate that a Clb/Cdk1-mediated regulation of the Fkh2 transcription factor synchronizes the temporal mitotic CLB expression in budding yeast. A simplified kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(87 citation statements)
references
References 41 publications
2
84
1
Order By: Relevance
“…This model was converted to a Boolean logic, where a prior knowledge network (PKN) with four nodes—comprehending the cyclins Clb5, Clb3 and Clb2, and the CKI Sic1—was generated (Linke et al. 2017) incorporating the novel interactions found experimentally (Barberis et al. 2012).…”
Section: Logical Modeling Of the Budding Yeast Cell Cyclementioning
confidence: 99%
See 4 more Smart Citations
“…This model was converted to a Boolean logic, where a prior knowledge network (PKN) with four nodes—comprehending the cyclins Clb5, Clb3 and Clb2, and the CKI Sic1—was generated (Linke et al. 2017) incorporating the novel interactions found experimentally (Barberis et al. 2012).…”
Section: Logical Modeling Of the Budding Yeast Cell Cyclementioning
confidence: 99%
“…Among these six models, only two were able to match the experimental profile of CLB2 overexpression (Linke et al. 2017). Intriguingly, regardless of the number of interactions within these two models, a common, novel regulatory design is identified that connects the three Clb cyclins, which allows for their timely occurrence in a wave-like fashion.…”
Section: Logical Modeling Of the Budding Yeast Cell Cyclementioning
confidence: 99%
See 3 more Smart Citations